2019
DOI: 10.23888/hmj201973340-348
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of XPD Gene in Colorectal Cancer

Abstract: Рязанский государственный медицинский университет имени академика И.П. Павлова, Рязань, Российская Федерация _____________________________________________________________________________ Цель. Оценка полиморфизма гена XPD (xeroderma pigmentosum group D) у пациентов с колоректальным раком. Материалы и методы. Оценка полиморфизма гена проводилась у 143 человек. Основную группу составили 105 пациентов с колоректальным раком, проходивших обследование и лечение в Рязанском областном клиническом онкологическом диспа… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This protein is part of transcription factor IIH (TFIIH), which is required for both DNA repair and transcription. A number of studies have reported a significant association between the XPD gene polymorphisms Asp312Asn and Lys751Gln and cancer risk [11,19]. However, the results were inconsistent and contradictory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein is part of transcription factor IIH (TFIIH), which is required for both DNA repair and transcription. A number of studies have reported a significant association between the XPD gene polymorphisms Asp312Asn and Lys751Gln and cancer risk [11,19]. However, the results were inconsistent and contradictory.…”
Section: Resultsmentioning
confidence: 99%
“…For genotyping, 6 functional single nucleotide polymorphisms were selected based on literature data on their occurrence in different populations and their effect on the development of breast cancer [1,11,12]: two polymorphisms of the oxidative stress genes CAT (rs4756146, rs2284365); DNA repair genes XRCC1 (rs1799782, rs 25487) and XPD (ERCC2)(rs13181, rs1799793). All SNPs were in Hardy-Weinberg equilibrium in cases and controls.…”
Section: Methodsmentioning
confidence: 99%
“…НАУЧНЫЙ ОБЗОР | Том 11, № 2, 2023 | НАУКА МОЛОДЫХ (Eruditio Juvenium) https://doi.org/10.23888/HMJ2023112229-240 Введение В настоящее время достаточно быстрое развитие молекулярной онкологии происходит за счет появления новых технологий и модернизации уже известных методов. Эти технологии позволяют не только обновлять и уточнять представление о молекулярно-генетической природе опухолей, но и развивать новые направления для терапии и способов прогнозирования течения онкологических заболеваний [1,2]. Предпосылкой этого научного направления стала расшифровка генома человека, в результате которой к настоящему времени идентифицировано и картировано большое количество генов человека.…”
unclassified